Managing people in hostile environments: lessons learned and new grounds in HR research - Bader, Benjamin; Schuster, Tassilo; Dickmann, Michael (Taylor & Francis, 2019)
Questions related to managing people in hostile environments have become more central on the agenda of business leaders and HR professionals in MNCs. This is due to developments such as the increase of terrorism or the political instability in many regions. In consequence, research on the role of HR in hostile environments has increased as well, though it can still be considered in its early stages. We would like to review the current state of research on managing people in hostile environment. In particular, with this article we contribute to the literature by developing a conceptual framework that distinguishes between micro-, meso- and marco-level research and charts progress, mechanisms and results. We call this the Situation – Response – Outcome (SRO) Framework of HRM in hostile environments. Depending on the level of analysis, the framework further differentiates between a pre-crises, acute-crisis, and post-crises phases of HRM in hostile environments. As a result, it serves as the basis to cluster existing literature around it and to show avenues for future research.
Keywords: Terrorism; hostile environments; people managemen; situation – response – outcomes framewor; research agenda